Territorial organization of confessional space of the Western regions of Ukraine - Kostashchuk, Ivan (Human Geography Journal, 2020)
The study is devoted to the coverage of the territorial organization of the modern confessional space of the regions of Western Ukraine, which was formed under the influence of complex historical and geographical factors, namely the formation of Ukraine, socio-political life of individual regions, the influence of Western civilization, national liberation movements, ethnic composition and more.The Western Ukrainian region, to which we include 8 oblasts, namely: Zakarpattia, Lviv, Volyn, Rivne, Ternopil, Ivano-Frankivsk, Chernivtsi and Khmelnytskyi, is distinguished by a high level of religious mosaic and activity of the population, which is manifested in high rates of provision with religious communities and organizations, a high proportion of those who consider themselves believers and attend worship services weekly or at least once a month, and other indicators. It is interesting that in the territory of Western Ukraine such historical and geographical lands are separated as Volyn, Zakarpattia, Halychyna, Northern Bukovina, Southern Bukovina, part of Dorohoishchyna and Podillya, which certainly emphasizes this region as special for studying the geographical features of the formation of confessional space. Orthodoxy in the study region predominates in Chernivtsi, Khmelnytskyi, Volyn, Rivne, and Zakarpattia oblasts, and Greek Catholicism predominates in Halychyna (Ivano-Frankivsk, Lviv, and Ternopil oblasts). It is interesting that Roman Catholics are quite prominent in the confessional structure in the Khmelnytskyi oblast, where Poles occupy a significant share in the ethnic structure. Protestantism is present in all regions, but it is most concentrated in Volyn and Northern Bessarabia. In Zakarpattia oblast there is a separate denomination – the Transcarpathian Reformed Church, which is mainly professed by Hungarians.It is established that the confessional space differs not so much by administrative-territorial boundaries as by historical-geographical regions, which confirms the idea of the main influence on the process of its formation of historical-geographical features of territory formation, ethnic composition, demographic processes and other socio-political factors. .